Evaluation of nationwide referral pathways, investigation and treatment of suspected cauda equina syndrome in the United Kingdom. (2nd November 2019) - Fountain, Daniel M.; Davies, Simon C. L.; Woodfield, Julie; Kamel, Mohammed; Majewska, Paulina; Edlmann, Ellie; Jamjoom, Aimun A. B.; Hoeritzauer, Ingrid; Waqar, Mueez; Mahoney, Dominic E.; Vyas, Dillon; Schramm, Moritz W. J.; et al.
Abstract: Purpose: Cauda equina syndrome (CES) is a spinal emergency with clinical symptoms and signs that have low diagnostic accuracy. National guidelines in the United Kingdom (UK) state that all patients should undergo an MRI prior to referral to specialist spinal units and surgery should be performed at the earliest opportunity. We aimed to evaluate the current practice of investigating and treating suspected CES in the UK. Materials and Methods: A retrospective, multicentre observational study of the investigation and management of patients with suspected CES was conducted across the UK, including all patients referred to a spinal unit over 6 months between 1st October 2016 and 31st March 2017. Results: A total of 28 UK spinal units submitted data on 4441 referrals. Over half of referrals were made without any previous imaging ( n = 2572, 57.9%). Of all referrals, 695 underwent surgical decompression (15.6%). The majority of referrals were made out-of-hours ( n = 2229/3517, 63.4%). Patient location and pre-referral imaging were not associated with time intervals from symptom onset or presentation to decompression. Patients investigated outside of the spinal unit experienced longer time intervals from referral to undergoing the MRI scan. Conclusions: This is the largest known study of the investigation and management of suspected CES. We found that the majority of referrals were made without adequate investigations. Most patients were referred out-of-hours and many were transferred for an MRI without subsequently requiring surgery. Adherence to guidelines would reduce the number of referrals to spinal services by 72% and reduce the number of patient transfers by 79%.